A framed field experiment about policy measures: Testing the effectiveness of rewards or punishments with different probabilities as incentives in palm oil production - Stefan Moser; Oliver Mußhoff (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2014)
Palm oil production creates negative externalities, e.g., through intensive fertiliser applica-tion. If policy wants to limit externalities, an effective, sustainable and efficient measure seems desira-ble. Embedded in a framed field experiment in Indonesia, we apply a business simulation game to test ex ante several incentives for reducing the use of fertiliser in palm oil production. These incentives are arranged in the form of different designs, i.e., either a reward or punishment, varying in their magni-tude and probability of occurrence but constant in the effect on expected income. Results show that participants react significantly different depending on the incentive design. A high reward with a low probability to occur has been found to be the most effective and sustainable incentive design. For effi-ciency, a low and certain reward is indicated to be the best design.
urn:nbn:de:gbv:7-webdoc-3937-0
Keywords: 330; policy influence analysis; effective incentive; framed field experiment; business simulation game; palm oil production; Indonesia